The Use Of Lightweight Material At Road Access Construction On Slope - Hansen Tananda; Aris Handoko; Paulus Pramono Rahardjo (Indonesian Geotechnical Journal, 2023)
To achieve the design elevation from the existing ground level, an embankment work with a thickness of 8-10 meters thick on the slope should be conducted considering both the safety aspect as well as the economic aspect. Based on the conceptual drawing by Contractor, the embankment will sit on the slope without any grading works. The drawing shows that the embankment will be constructed directly on the existing slope. Any fill work on the original slope without any proper reinforcement will cause stability issues.  The discussion about the embankment area construction concept has come up with some options such as the use of a slab-on-pile system and the use of a combination sheet pile - bore piles and the use of mini piles under the embankment. Based on further discussion with Contractor and Owner about the technical aspect and construction cost required, it is recommended to construct an embankment with lightweight material (geofoam). The use of lightweight geofoam is a suitable solution to be considered. Another advantage of using geofoam is that the construction period is faster than conventional methods. Geofoam installation work already started on November 2022. On February 2023, the geofoam slope construction finished.